A priority-based queuing system for P2P-SIP call communications control. (19th September 2019) - Amad, Mourad; Aïssani, Djamil; Bouiche, Razika; Madi, Nouria
Regarding the shortcoming of fundamental existing solutions for VoIP communications (e.g., SIP) based on centralisation, both academia and industry have initiated research projects that focus on the integration of peer-to-peer (P2P) paradigms into session initiation protocol (SIP) communication systems (e.g., P2P-SIP). P2P-SIP builds an overlay network to provide efficient, interoperable and flexible SIP-based services. In this paper, we propose a new model for critical calls, that takes into consideration the priority aspect of some specific requests (e.g., emergency calls). The proposed model is generic regarding the P2P underlying and physical architectures. For illustration purposes, we consider Gnutella, as a representative of unstructured P2P networks, and Chord, as a representative of structured P2P networks. In order to validate the proposed solution, a M/M/1 queuing model is considered. Performance evaluations show that the preliminary results are globally satisfactory and that our proposed model under certain conditions is relevant.